2019
DOI: 10.12659/msm.913338
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection of Primary Ewing’s Sarcoma of Bone Improves Overall Survival in Patients Presenting with Metastasis

Abstract: Background Metastatic Ewing’s sarcoma (ES) of bone has a poor prognosis. Because there have been few previous studies on the prognostic factors and clinical outcome in patients with ES who have metastases at presentation, the aim of this study was to use the Surveillance, Epidemiology, and End Results (SEER) database to compare the clinical outcome following single and combined radiation treatment and surgery. Material/Methods The SEER database was used to identify pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The results of Kaplan-Meier curve showed that gender had no significant impact on OS, which was consistent with that of S.E. Bosma, Friedman Danielle Novetsky and Ren Yingqing et al [3,4,7], who found that female patients with Ewing sarcoma had similar OS to male patients. In the process of developing the nomogram, we found that age played a pivotal role in total points.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of Kaplan-Meier curve showed that gender had no significant impact on OS, which was consistent with that of S.E. Bosma, Friedman Danielle Novetsky and Ren Yingqing et al [3,4,7], who found that female patients with Ewing sarcoma had similar OS to male patients. In the process of developing the nomogram, we found that age played a pivotal role in total points.…”
Section: Discussionsupporting
confidence: 88%
“…3 Nomogram for the prediction of 3-and 5-year OS in patients with Ewing sarcoma. OS, overall survival of other studies [3][4][5][6], except S.E. Bosma et al, who indicated by a system review that the level of evidence for an association with OS for age was inconclusive.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In line with past research and recent unpublished data and conference abstracts, we observed that surgical resection of the primary tumor was associated with an overall survival benefit for patients presenting with metastatic primary malignant bone tumors. Using the national SEER database, Ren et al [28] found that surgical resection of primary tumors in patients with metastatic Ewing sarcoma was associated with substantially improved overall survival. Two additional SEER-based abstracts presented at the 2019 Musculoskeletal Tumor Society (MSTS) meeting found that surgical resection of the primary tumor site improves survival for both patients with metastatic osteosarcoma and those with soft-tissue sarcomas.…”
Section: Surgical Resection Of the Primary Tumor And Overall Survivalmentioning
confidence: 99%
“…For patients with metastatic ES, surgical treatment is also signi cant for the survival rate [41] . This is consistent with the results of this study, although the effect of tumor site and size on prognosis is complex.…”
Section: Establishment and Veri Cation Of Survival Analysis And Predimentioning
confidence: 99%